Blood Flow Restriction Training Using the Delfi System Is Associated With a Cellular Systemic Response - Mark C. Callanan, M.D; Hillary A. Plummer, Ph.D., A.T.C; Garrett L. Chapman, M.D; Tyler J. Opitz, D.P.T; Nicole K. Rendos, Ph.D., A.T.C; Adam W. Anz, M.D (Elsevier, 2021)
Purpose: To determine the effects of blood flow restriction (BFR) exercise on CD34+ cells, platelets, white blood cells, neutrophils, lymphocytes, lactate, and glucose. Methods: Healthy participants aged 20 to 39 years who were able to perform the exercise sessions were recruited. Participants underwent an experimental (EXP) occluded testing session and a control (CON) session using the Delfi Personalized Tourniquet System. Blood draws were performed prior to testing and immediately after the exercise session. Blood analysis consisted of a complete blood count as well as flow cytometry to measure peripheral CD34+ counts as a marker for hematopoietic progenitor cells. Results: Fourteen men (aged 30.8 ± 3.9 years) volunteered. There was a significant increase in average CD34+ counts immediately after the EXP session only (3.1 ± 1.2 cells ⋅ μL-1 vs 5.2 ± 2.9 cells ⋅ μL-1, P = .012). Platelet counts were significantly elevated after both sessions, with the average increase being higher after the EXP session (mean difference [MD], 34,200/μL; P < .002) than after the CON session (MD, 11,600/μL; P < .002). White blood cell counts significantly increased after both the EXP (8,400 ± 2,200/μL vs 6,300 ± 1,600/μL; P < .001) and CON (MD, 900/μL; P < .001) sessions. There was a significant increase from baseline to immediately after exercise in the average number of lymphocytes (MD, 6.3%; P < .001) and, conversely, a significant decrease in the average neutrophil count (MD, 6.5%; P < .001) in the EXP session only. Lactate levels significantly increased in the EXP (MD, 6.1 mmol ⋅ L-1; P = .001) and CON (MD, 3.6 mmol ⋅ L-1; P = .001) groups. No changes in glucose levels were observed. Conclusions: Exercise with BFR causes a significant post-exercise increase in peripheral hematopoietic progenitor cells and platelets, beyond that of standard resistance training. Clinical Relevance: BFR can be considered a way to manipulate point-of-care blood products such as platelet-rich plasma to increase product yield.